Increasesd brain levels of hydrogen peroxide in a transgenic mouse model of Huntington's disease - Laço, Mário Luís Nôro (2015)
Trabalho final de mestrado integrado em Medicina (Bioquímica), apresentado á Faculdade de Medicina da Universidade de Coimbra